Shared secrecy: teasing, attachment, and children's emotional management in rural southern Mongolia. (17th January 2022) - Michelet, Aude
Abstract: In recent decades, anthropologists have scrutinized psychologists' claim that humans process information about others by imputing mental states. The debate remains open whether cross‐cultural variability in how people conceive of minds and inner states reflects differences in their folk theories only, or whether it engenders deep‐grained psychological differences. In this article, I look at the very onset of children's apprenticeship in emotional management to examine its cognitive consequences. In the context of rural Mongolia in the late 2000s, questions about homesickness prompted by adults raised children's awareness of the existence of a private self and by the very same process discouraged verbalization or public display of personal feelings. I start by presenting interactions where children were routinely teased about homesickness, and invited to deny that they missed their family. I contextualize this teasing routine within local conceptions about emotional control and linguistic ideology to unveil how it introduced children to the performative power of words while also making them face moral dilemmas. The irreconcilable tension between behaving according to expectations of self‐control and experiencing separation induced children's discovery of the possibility of disconnecting intimate feelings from public self‐presentation, thus transforming the experience of separation into an experience of secret connection. I speculate that the secrecy that hallows homesickness contributed to making it all the more poignant. The way adults constantly checked on whether children were missing their home prompted children to actually identify some emotional state or aspect of their experience as 'missing home'. It gave a name to a personal experience which thus became social and guaranteed that it became a shared feeling, albeit a secret one. Abstrait: Secrets partagés : taquineries, attachement et gestion émotionnelle par les enfants dans le sud rural de la Mongolie Résumé Les anthropologues questionnent, depuis maintenant quelques dizaines d'années, l'affirmation des psychologues selon laquelle les humains traitent les informations relatives aux autres en leur attribuant des états mentaux. Ils n'ont cependant toujours pas tranché la question de savoir si la variabilité interculturelle dans la conception de l'esprit et des états internes reflète des différences entre des théories vernaculaires uniquement, ou si elle engendre des différences psychologiques profondes. L'autrice s'intéresse ici au tout début de l'apprentissage de la gestion émotionnelle par les enfants et en examine les conséquences cognitives. Dans la Mongolie rurale de la fin des années 2000, en questionnant les enfants sur leur mal du pays, les adultes leur faisaient prendre conscience de l'existence d'un moi privé et, de ce fait, les dissuadaient de verbaliser ou d'exprimer publiquement leurs sentiments personnels. L'article commence par une présentation d'interactions dans lesquels les enfants faisaient l'objet de taquineries routinières sur le mal du pays et étaient incités à nier que leur famille leur manquait. L'autrice contextualise cette routine de taquineries dans le cadre des conceptions locales du contrôle émotionnel et de l'idéologie linguistique, afin de dévoiler la manière dont ces taquineries font découvrir aux enfants la puissance performative des mots, tout en les plaçant face à des dilemmes moraux. La tension entre les impératifs inconciliables de se conformer aux attentes de maîtrise de soi et de vivre la séparation induisait la découverte par les enfants de la possibilité de détacher leurs sentiments intimes de leur représentation de soi publique, transformant ainsi l'expérience de la séparation en une expérience de lien secret. L'autrice spécule que le secret auréolant le mal du pays contribue à rendre celui‐ci d'autant plus poignant. La manière dont les adultes demandaient sans cesse aux enfants si leur maison leur manquait incitait les enfants à identifier un état émotionnel ou un aspect de leur expérience comme « le mal de la maison ». Elle donnait un nom à une expérience personnelle qui devenait ainsi sociale et guarantissait que ce sentiment devienne partagé, tout en restant secret.